2015
DOI: 10.1111/pace.12746
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in QT Dynamics after Initiation and Termination of Paroxysmal Atrial Fibrillation

Abstract: In patients with paroxysmal AF, bradycardia-dependent QT prolongation was attenuated during AF, and was corrected and gradually augmented along with continuation of SR, especially in patients receiving AADs. This could increase the risk of developing torsade de pointes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Yamaguchi et al found an attenuated QT/RR slope with a maximum of 4-5 hr after restoration to SR in paroxysmal AF with a diurnal Holter recording in five patients on AA drugs (Darbar et al, 2008;Lenhoff et al, 2016;Yamaguchi et al, 2015). In our study, the diurnal rhythm was more pronounced in patients on sotalol as compared to patients on metoprolol, at night.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Yamaguchi et al found an attenuated QT/RR slope with a maximum of 4-5 hr after restoration to SR in paroxysmal AF with a diurnal Holter recording in five patients on AA drugs (Darbar et al, 2008;Lenhoff et al, 2016;Yamaguchi et al, 2015). In our study, the diurnal rhythm was more pronounced in patients on sotalol as compared to patients on metoprolol, at night.…”
Section: Discussionsupporting
confidence: 46%
“…We have previously described QTc prolongation after CV that seems reversed one week later (Kirchhof et al., 2016 ) and Darbar et al showed prolongation of QTc shortly after CV compared to during AF (Bexton et al., 1986 ). Yamaguchi et al found an attenuated QT/RR slope with a maximum of 4–5 hr after restoration to SR in paroxysmal AF with a diurnal Holter recording in five patients on AA drugs (Darbar et al., 2008 ; Lenhoff et al., 2016 ; Yamaguchi et al., 2015 ). In our study, the diurnal rhythm was more pronounced in patients on sotalol as compared to patients on metoprolol, at night.…”
Section: Discussionmentioning
confidence: 99%
“…Repolarization delay predisposes patients to TdP and the short-long-short sequences that classically trigger TdP may be more common in AF than in SR. Many patients are treated for AF with class III antiarrhythmic drugs; these agents are often initiated while patients are in AF and reliable detection of excessive QT prolongation is necessary to minimize proarrhythmia [18,23]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, detection of repolarization delay during AF is of substantial clinical significance, for example during initiation of treatment with class III antiarrhythmic agents. Several methods have been suggested to deal with the problem [1318]. We sought to determine if the exponential weight models with an immediate response component derived from SR and atrial pacing data also provide a consistent description of QT dynamics in AF.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent evidence demonstrates improvements in the QT correction procedures when a range of the past values of HR is taken into account 4 , 21 , 22 . The correction improvement is especially profound in patients with atrial fibrillation, where HR values are unpredictable 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%